DIVERSITY OF ECOLOGICAL ECONOMICS AND DEGROWTH THEORY: FOCUSING ON THE RELATIONSHIP BETWEEN THERMODYNAMIC LAWS AND VISION (International journal of artificial intelligence, 2024)
The degrowth theories within ecological economics can be distinguished between two flows: Georgescu-Roegen, S.Latouche and K.E.Bullding, H.E.Daly, T.Jackson. In the former, degrowth leads to a complete rejection of any development or growth, culminating in negative growth, whereas, in the latter, degrowth does not necessarily end in a total rejection of all progression or growth. At first glance, these differences seem to stem from varying interpretations of thermodynamic laws, but underlying them are different analytical visions regarding environmental issues. The flow from Boulding to Daly to Jackson believes that the sustainability of human societies can be secured through balanced growth or steady-state economics, whereas Georgescu-Roegen and Latouche do not share this belief. This divergence in beliefs or visions has led to distinct degrowth theories. This paper will analyze this process while comparing the two degrowth theories.